2017
DOI: 10.1038/srep40304
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of sleep plasticity by a thermo-sensitive circuit in Drosophila

Abstract: Sleep is a highly conserved and essential behaviour in many species, including the fruit fly Drosophila melanogaster. In the wild, sensory signalling encoding environmental information must be integrated with sleep drive to ensure that sleep is not initiated during detrimental conditions. However, the molecular and circuit mechanisms by which sleep timing is modulated by the environment are unclear. Here we introduce a novel behavioural paradigm to study this issue. We show that in male fruit flies, onset of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(97 citation statements)
references
References 69 publications
(102 reference statements)
7
89
1
Order By: Relevance
“…One example of the maintenance of sleep homeostasis in respond to temperature shift is the homeostatic restoration observed in previous researches, as the differences between sleep at the treated and normal temperature in daytime are reversed at nighttime. The restoration is found when the temperature difference is as subtle as 4-5°C, but disappeared when the difference is gradually increased [7][8][9]. In our research, sleep patterns are uniformly changed under the 7°C difference and no homeostatic restoration was observed.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…One example of the maintenance of sleep homeostasis in respond to temperature shift is the homeostatic restoration observed in previous researches, as the differences between sleep at the treated and normal temperature in daytime are reversed at nighttime. The restoration is found when the temperature difference is as subtle as 4-5°C, but disappeared when the difference is gradually increased [7][8][9]. In our research, sleep patterns are uniformly changed under the 7°C difference and no homeostatic restoration was observed.…”
Section: Discussioncontrasting
confidence: 48%
“…Series of studies related to the effect of temperature on sleep have been reported, but the paradigms and temperature difference they implemented vary a lot [7][8][9]. We define the cold condition at 18°C, which is the lower limit of Drosophila's temperature preference [20].…”
Section: Cold Promotes Sleep In Wild Type Drosophilamentioning
confidence: 99%
See 1 more Smart Citation
“…Using the standard definition of a Drosophila sleep bout as a 5 min period of inactivity (measured using the Drosophila Activity Monitor (DAM) system [6]), we recently showed that elevating ambient temperature from 22°C to ≥ 30°C delays onset of the first morning sleep bout in Drosophila males [3]. However, Drosophila sleep is often initially fragmented during the early morning at lowto-medium temperatures ( Figure 1A).…”
Section: Consolidated Sleep Onset In Drosophila Is Gated By Circadianmentioning
confidence: 99%
“…This led to our second problem, finding confounding phenotypes from mechanical agitation resulting from the movement. Third, published methods for changing temperature are often slow [5,12].…”
Section: Introductionmentioning
confidence: 99%